EFEKTIFITAS PENYULUHAN KESEHATAN GIGI DAN MULUT UNTUK MERUBAH PERILAKU MENYIKAT GIGI PADA SISWA KELAS IV DI SDN 5 BENOA KABUPATEN BADUNG TAHUN 2016 - Asep Arifin Senjaya; Ni Ketut Indarayani (Jurnal Kesehatan Gigi (Dental Health Journal), 2017)
The 2013 Basic Health Research in the Province of Bali showed that the population with dental and mouth problems in the last 12 months in Bali was 24.0%. While Badung Regency is in the top four positions at 31.6%. Brushing teeth is the main action to clean plaque. Plaque plays a role in the pathogenicity of caries and periodontal disease. Ni Kadek Indrayani's research on grade IV students at SD N 5 Benoa in 2016, obtained results that were before being given counseling 90% of students behaved brushing incorrectly. Then after being given counseling 85% of students behave correctly. The purpose of this study was to determine the effectiveness of dental and mouth health education to change the behavior of tooth brushing on fourth grade students at SDN 5 Benoa Badung Regency 2016. This type of cross sectional study, uses secondary data from Ni Kadek Indrayani's research. Chi square test results, showed the value of sig. 0,000. The conclusion of counseling is effective in changing the behavior of brushing teeth in grade IV SDN 5 Benoa Badung Regency in 2016.